COMMUNITY PARTICIPATION IN THE MANAGEMENT OF CULTURAL TOURISM ATTRACTION OF TODO VILLAGE, MANGGARAI DISTRICT - Fatrisia Yulianie; I Wayan Sonder; I Wayan Sumariadhi (Jurnal Kajian dan Terapan Pariwisata, 2024)
This article discusses community participation in the management of Kampung Todo Cultural Tourism Object of Manggarai Regency which aims to explore the potential of Kampung Todo Tourism Object and community participation in its management. The data analysis method used in this research is a qualitative descriptive method that aims to describe the relationship between the phenomena studied systematically, factually, and accurately. Data collection was carried out using interview techniques, observation, and documentation in the form of primary data and secondary data. The results of the analysis show that Todo Village has tourism potential, both cultural potential and natural potential. Community participation has become more optimal in management with the formation of a management body, namely the Tourism Awareness Group, with the aim of ensuring that all local communities feel the benefits of tourism activities. Community participation through tourism awareness groups has started from planning (decision making), organizing (forming Pokdarwis), implementation (as managers, guides, providers of needs and services for tourists) and participating in supervision.